Implementation of Independent Learning to Increase Productivity and Students Learning Outcomes during the COVID-19 Pandemic - I Ketut Sudarsana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The study aimed to determine the extent of the productivity and students’ learning outcomes increased during the COVID-19 pandemic through the independent learning implementation. The implementation of this independent learning model is based on the existence of appeals and government policies that require and oblige lecturers and students to carry out the learning process at their respective homes. The main subjects of this study were all students in the first semester of Class A of the Hindu Religious Education Study Program, Faculty of Dharma Acarya, Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar with a total of 28 people. The results showed that 98% of students experienced an increase in learning productivity. It was supported by an increase in learning outcomes with a percentage of 96%. This increase was evidenced by comparing the middle test score with the final test score. The increase in student learning outcomes cannot be separated from parents’ support, supervision of lecturers, and online learning programs using zoom. The YouTube-assisted learning program is also a way to support the independent learning implementation, besides learning books obtained online. This independent learning model is considered productive during the COVID-19 pandemic to support government policy in conduct social distancing and increasing student learning productivity.